Hubungan Panjang Bobot dan Beberapa Aspek Reproduksi Ikan Tongkol Lisong (Auxis rochei Risso, 1810) di Perairan Teluk Bone - Syainullah Wahana; Yusnan Suyuti DM; Muhammad Nur; Adiara Firdhita Alam Nasyrah (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2021)
This research direct analyzes the length-weight relationship and reproduction aspect of bullet tuna (Auxis richei Risso, 1810) that can be valuable data for policymaking in the waters of Bone Bay. Sampling was held from September to November 2021 in Lonrae Village, Tanete Riattang Timur District, Bone Regency. The growth pattern was determined by analyzing the length-weight relationship, TKG was determined by morphological characteristics, and gonad somatic index was calculated based on the Johnson method. The result of the length-weight relationship was obtained b value = 3.3345 in September, b value = 2.837 in October, and b value = 3.3690 in November. The analyze of the t-test obtained t count > t table that means in September and November was classified into a positive allometric growth pattern, conversely, the growth pattern in October was negative allometric. The condition factor of bullet tuna in Bone Bay waters was obtained in the range of 0.95-1.03 with an average of 0.97, in males 1.23-1.44 with an average of 0.95-1.33 and the range was 0.72-0.83 with an average of 0.77 in fimales. The gonad somatic index value in male and female ranged from 0.053 to 0.242 and from 0.052 to 0.068, respectively. The bullet tuna that have been found categorized as immature gonads.